If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.0625 * 24 = x Multiply 0.0625 * 24 1.5 = x Solving 1.5 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 1.5 + -1x = x + -1x Combine like terms: x + -1x = 0 1.5 + -1x = 0 Add '-1.5' to each side of the equation. 1.5 + -1.5 + -1x = 0 + -1.5 Combine like terms: 1.5 + -1.5 = 0.0 0.0 + -1x = 0 + -1.5 -1x = 0 + -1.5 Combine like terms: 0 + -1.5 = -1.5 -1x = -1.5 Divide each side by '-1'. x = 1.5 Simplifying x = 1.5
| 3p-13=3*107-13 | | 2x^2+16-24=0 | | -117-10x=109-45x | | p+10=107+13 | | 3w+9=-2w-8 | | (2x+7)+(5x+8)= | | 16=2(6)+2w | | 3x+89=12x-10 | | 2n+36=3n+4+16 | | (p+10)+(3p-13)+p=532 | | 18a-5a=8a/8 | | 246-7x=38x+16 | | 3n+4=1n+22 | | -10t-4=-8+9t | | -45=6x+9 | | (.75)(c)+(.40)(600-c)=380.00 | | 5n=2n+30 | | 55=2l+2(7) | | 1/2/4 | | 2n-9=11 | | 5+t=13+9 | | (1/2)/4 | | 3/2x+2/3x=13 | | 5+11x=86 | | 1x+2+2x=3+1 | | Q=x+y+zfory | | 6x+133=103-6x | | 6x+13=103-6x | | 3sqr(x+5)=2sqr(7-2x) | | 3w+9=2w-8 | | 11x=-x-24 | | 2x+x+1=4x-18 |